Professional Mentality as a Dynamic Structure - Tolochek, Vladimir A. (Saratov State University, 2020)
The article presents methodology and methods of field study on the example of studying the professional mentality (PM). Purpose of the study: Analysis of typical conditions of scientific research work (SRW), connections between methods, recorded facts and properties of psychological objects. Methods: analysis of literary sources; observation, questionnaires, expert polls, psychodiagnostics, parametric methods of statistics. Hypotheses: 1. Research methods, revealed scientific facts, described properties of psychological objects are in a relationship of mutual conditioning. 2. Attention to artifacts allows us to develop constructive options for further study of psychological objects. Study base: a) civil servants (93 people); b) private security guards (more than 200 people). The meta-problem of the present study (the methodology and methods of field study) is viewed on the example of observation and study of behavior and activities of the subjects in different social situations. We demonstrated that the maximum differentiation of aspects of the working conditions of civil servants (up to the "incredible" and atypical 11-point scale of intervals), awareness of the socio-demographic and work-related aspects of the subjects, the use of a set of parametric methods of statistics made it possible to satisfactorily solve SRW tasks even in situations when respondents resisted. The study of professional mentality (PM) using two models (professional spheres opposite in many respects, which set two "poles" of their possible characteristics) allows us to identify both similar and different features of behavior, relationships, activities and interaction of people. It is stated: 1) The constructive approach is the joint study of the properties of at least two psychological objects 2) In the study of complex psychological objects, it is advisable to use a differential approach and complexes of methods of parametric statistics.